PENGARUH MODEL PEMBELAJARAN FSLC TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI MOTIVASI BELAJAR SISWA - Komariya Komariya; Nurul Farida; Ira Vahlia (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This study aims to decide the effect of learning models on the ability to solve mathematical problems seen from student learning motivation. Learning model used is FSLC and conventional learning model. This type of research is a quasi experiment. The population in this research is the students of class VIII SMP N 1 Trimurjo academic year 2017/2018. The sample of this research is taken by using cluster random sampling technique with sample in experiment class as much as 32, and control class counted 31. The result of this research are as follows: 1) There is difference of problem solving ability between student learning by using FSLC learning model and model of learning conventional. 2) Problem-solving abilities in highly motivated students are better than those with moderate motivation and problem-solving skills in better-motivated students than low motivated students. 3) There is no interaction between FSLC and conventional learning model and learning motivation toward math problem solving ability. The FSLC learning model provides better mathematical problem-solving skills than conventional learning models in both high and medium motivations.